The Effect of Environmental Knowledge and Perceived Value on Visitor Experience in Forest Recreation - Rahmafitria, Fitri; Kaswanto; Mosyaftiani, Amarizni; Wiyoga, Harityas (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
Vandalism and environmental degradation pose challenges in natural recreation areas, prompting the need for interventions to promote environmental consciousness and nature appreciation. This study investigates the role of knowledge and perceived value in enhancing ecological experiences. A five-point Likert scale survey was distributed to 235 visitors at Djuanda Forest Park in Bandung, Indonesia. Structural Equation Modeling (SEM-PLS) was employed to analyze direct and indirect influences. The results demonstrate that enhancing ecological perceived value positively impacts visitors' interactions with nature. Moreover, increased actual knowledge regarding environmental degradation enhances the perceived value of outdoor recreation in natural settings. These findings highlight the importance of developing educational programs in natural recreation areas to support sustainable environmental practices.